Drei Nebensonnen: Forte’s Linear-Motivic Analysis, Korngold’s Die Tote Stadt, and Schubert’s Winterreise as Visions of Closure - Edward D. Latham (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
Schenkerian analysis, yet they are uniquely qualified to highlight the presence or absence of closure at multiple structural levels. Works that present a thwarted linear narrative filled with obstacles and roadblocks embody a tragedy that is poignant to performers and audiences alike, and the type of analysis presented here captures aspects of that tragedy. An important stimulus to this investigation is Allen Forte’s focus on onset and closure throughout fifty years of writing on both tonal and post-tonal music. While in one sense this generalized focus helped him sidestep the controversy over prolongation in post-tonal music, it also served to draw his reader’s attention to the beginnings and endings of phrases, sections, and complete works; and these are the very places where the successes and failures of characters in dramatic vocal works are most apparent. This article outlines the development of Forte’s ideas throughout his career, and then discusses the concept of musical closure in harmonic and melodic terms, drawing on the dramatic theories of Constantin Stanislavsky and the music-theoretical writings of William Caplin, Janet Schmalfeldt, and Heinrich Schenker. Schubert’s Winterreise and Korngold’s Die tote Stadt are examined. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part I).